MEASURING IMPACT, DEFINING LIABILITY: A LITERATURE REVIEW ON THE LEGAL IMPLICATIONS OF ARTIFICIAL INTELLIGENCE IN THE JUDICIAL SYSTEM AND REGULATORY FRAMEWORK IN THE DIGITAL AGE - Gunawan Widjaja (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
This article presents a comprehensive literature review on the legal implications of artificial intelligence (AI) in the judicial system and regulatory development in the digital age, with a focus on measuring impacts and defining legal liabilities. The findings reveal that AI enhances the efficiency of predictive justice and RegTech, yet poses risks of algorithmic bias, the black box problem, legal liability gaps, and threats to democratic legitimacy. The study identifies research gaps in developing countries such as Indonesia, where there is a lack of normative and institutional analysis. Recommendations include an adaptive risk-based model akin to the EU AI Act, human-in-the-loop oversight, and national regulations grounded in the Pancasila ethical framework to balance innovation with substantive justice.